Sharing the Knowledge: Sharing Aggregate Genomic Findings with Research Participants in Developing Countries. - Kerasidou, A (Blackwell Publishing Ltd, 2014)
Returning research results to participants is recognised as an obligation that researchers should always try to fulfil. But can we ascribe the same obligation to researchers who conduct genomics research producing only aggregated findings? And what about genomics research conducted in developing countries? This paper considers Beskow's et al. argument that aggregated findings should also be returned to research participants. This recommendation is examined in the context of genomics research conducted in developing countries. The risks and benefits of attempting such an exercise are identified, and suggestions on ways to avoid some of the challenges are proposed. I argue that disseminating the findings of genomic research to participating communities should be seen as sharing knowledge rather than returning results. Calling the dissemination of aggregate, population level information returning results can be confusing and misleading as participants might expect to receive individual level information. Talking about sharing knowledge is a more appropriate way of expressing and communicating the outcome of population genomic research. Considering the knowledge produced by genomics research a worthwhile output that should be shared with the participants and approaching the exercise as a 'sharing of knowledge', could help mitigate the risks of unrealistic expectations and misunderstanding of findings, whilst promoting trusting and long lasting relationships with the participating communities.